Cardiopulmonary Capacity in Overweight and Obese Children and Adolescents: A Cross-Sectional Study - Grzyb, Agata; Domagalska-Szopa, Małgorzata; Siwiec, Andrzej; Kwiecień-Czerwieniec, Ilona; Szopa, Andrzej (Frontiers in Physiology, 2021)
Background: One of the objective methods of assessing the level of cardiopulmonary capacity in overweight and obese children and adolescents is cardiopulmonary exercise testing (CPET). Aims: The purpose of present study is an evaluation of aerobic capacity in high BMI children and adolescents by comparing them with a normal weight control group by cardiopulmonary exercise testing (CPET). Methods and procedures: The subjects were recruited from participants of the Program of Treatment for Overweight and Obese Children organized by a local pediatric rehabilitation center in Poland. Based on BMI for age and gender , two validation groups were selected: 1) a group of overweight children (n= 49) and 2) a group of obese children (n=48). The study included also 53 normal weight participants as a reference group (REF). The study consisted of two parts: anthropometric measurements and CPET. The Godfrey protocol for CPET was applied. Outcomes and results: In this study, obese children and adolescents showed similar absolute VO2peak values in liters per minute (1.64 l/min) compared to overweight children (1.48 l/min), but significantly higher than children with normal body weight (1.39 l/min). The Obese children and adolescents presented lower VO2peak in relation to body weight (25.44 ml /kg /min) compared to their peers with normal body weight (36.5 ml/kg/min), and overweight children (29.18 ml/kg/min). Conclusions and implications: The main finding of our study was recognition of significant differences between cardiopulmonary capacity parameters in obese children in comparison not only to normal weight peers, but to overweight, too.